PENDEKATAN STRATEGIS MANAJEMEN KEPEMIMPINAN DALAM MENDORONG INOVASI PEMBELAJARAN - Siswadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This article aims to analyze strategic approaches in madrasa leadership management in fostering learning innovation. In the context of dynamic educational changes, leadership is no longer limited to administrative functions but also serves as a driving force for adaptive, creative, and student-centered learning transformation. Strategic leadership approaches include vision formulation, strengthening an innovative culture, and optimizing human resources and educational technology. This study employs a qualitative approach using library research and conceptual analysis of relevant literature, including visionary leadership in education. The findings reveal that visionary and strategic leadership can create an innovative learning ecosystem through collaboration, teacher empowerment, and technology integration. Furthermore, effective leadership is characterized by the ability to respond to change and build adaptive and sustainable organizational cultures. Therefore, strategic leadership management in madrasas plays a crucial role in promoting learning innovation and improving educational quality holistically.